Physiological response for elite rowers in a 4-weeks training camp at altitude 2100 meters - Chan, Y. Y.; Tai, C. H.; Lo, K. K.; Chan, L. H.; Lo, W. K.; Huang, Z.; Wu, J. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Rowing events are typically raced over 2000m, which last for 5.5-7 mins [1]. A number of studies indicated that rowing performances were dependent on energy systems, with 70-80% contributed by aerobic metabolism and 20-30% derived from anaerobic metabolism [2,3]. Therefore, it is common for rowing athletes to who live in sea level to train at moderate altitude, in order to improve their endurance performance [4]. In this study, the physiological response of elite rowing athletes who took part at a 4-weeks altitude training camp at altitude 2100 meters were investigated. METHODS: Twenty-seven elite rowing athletes from the Hong Kong Rowing Squad participate in this study (18 male,9 female, age 22.4±3.8). All subjects normally live at sea-level and participated a 4-weeks altitude training camp at altitude 2100 meters. Physiological parameters including hemoglobin (Hb) and body weight were monitored throughout the camp. Incremental test with rowing ergometer (Model D, Concept 2, USA) consists of seven stages of 1km were repeated at 7 days pre-camp, the 16th day during the camp, and 3 days post-camp. 30 mins rowing ergometer training at 22 spm were carried out every week to assess the performance of the rowers during the camp. A repeated measures ANOVA was used to detect changes between different time points of the parameters, effect sizes expressed as partial eta-squared (*2). Significance was set at P